Multiple Cause of Death Public Use Files, 2004 ([Verlag nicht ermittelbar], 2007)
This data collection includes information about the cause of all recorded deaths occurring in the United States, American Samoa, Guam, Northern Marianas, Puerto Rico and the Virgin Islands during 2004. Data are provided concerning underlying causes of death, multiple conditions that caused the death, place of death, residence of the deceased (e.g., region, division, state, county), whether an autopsy was performed, and the month and day of the week of the death. In addition, data are supplied on the sex, race, age, marital status, education, usual occupation, and origin or descent of the deceased. Along with to the combined Territory Public-Use file, a subset based on state of occurrence has been created for American Samoa, Guam, Northern Marianas, Puerto Rico and the Virgin Islands. The multiple cause of death fields were coded from the MANUAL OF THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES AND RELATED HEALTH PROBLEMS, TENTH REVISION (ICD-10).